Exploring the gap between policy and action in Disaster Risk Reduction: A case study from India. (September 2021) - Ogra, A.; Donovan, A.; Adamson, G.; Viswanathan, K.R.; Budimir, M.
Abstract: The transition from a response-based paradigm to an anticipative, prevention-based approach remains a stubborn challenge in Disaster Risk Reduction (DRR). Whilst the United Nations Office for Disaster Risk Reduction (UNDRR) has advocated the latter since the International Decade for Natural Disaster Reduction in the 1990s, many countries have been slow to move from a response-focused approach to a preventative one. International policy guidelines have successfully informed the national DRR policies in various countries; however, their further translation down to the regional and local level is full of complex political challenges, exacerbated in many areas by an increased frequency of disasters. In this paper we explore the case of India, using the example of landslide risk management. Through an analysis of the evolution of landslide risk governance during the last two decades in two hilly regions – Darjeeling in the Himalayas and the Nilgiris in the Western Ghats – we demonstrate that while the national government appears to have made considerable efforts to move in line with the UNDRR approaches, the eventual outcome of these efforts at the regional and local level is largely an incremental improvement on the existing DRR approach and not a paradigm shift in understanding and addressing disaster risk. We argue that overcoming these issues requires attentiveness to a situated understanding of disasters and institutions at the local level, and not treating apparent gaps between policy and action as functional challenges to be overcome with new science from national level.